2016
DOI: 10.1111/1471-0528.13867
|View full text |Cite
|
Sign up to set email alerts
|

Late spontaneous resolution of persistent molar pregnancy

Abstract: Women with treated molar pregnancy may avoid chemotherapy if 6-month hCG levels are raised but falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The cases of partial hydatidiform mole showed scattered hydropic villi with irregular scalloped villous outlines and mild trophoblastic hyperplasia in the sections stained with hematoxyline and Eosin as it's appear in Figure (1) and this results was agree with many previous studies [14]. The partial hydatidiform mole examination of trophoblastic distribution elucidate that the majority (60%) of samples show zonal distribution and high percentage (73.3%) of focal trophoblastic proliferation as it's describe in Table (2) and that was agree with many studies [2][3][4][5][6][7][8][9][10][11]. The vessels in the villous stroma of most of partial molar samples (80%) was obviously seen also the cistern appear clearly in 73.33% of the samples which was accordant to many studies [2-5-8-11].All partial molar pregnancy samples showed present of fetal a part which was conform by all references.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cases of partial hydatidiform mole showed scattered hydropic villi with irregular scalloped villous outlines and mild trophoblastic hyperplasia in the sections stained with hematoxyline and Eosin as it's appear in Figure (1) and this results was agree with many previous studies [14]. The partial hydatidiform mole examination of trophoblastic distribution elucidate that the majority (60%) of samples show zonal distribution and high percentage (73.3%) of focal trophoblastic proliferation as it's describe in Table (2) and that was agree with many studies [2][3][4][5][6][7][8][9][10][11]. The vessels in the villous stroma of most of partial molar samples (80%) was obviously seen also the cistern appear clearly in 73.33% of the samples which was accordant to many studies [2-5-8-11].All partial molar pregnancy samples showed present of fetal a part which was conform by all references.…”
Section: Discussionsupporting
confidence: 90%
“…Molar pregnancy or HM is rare and its frequency varies from a geographic area to another. The incidence in the United Kingdom (UK) is approximately 1 in 1000 pregnancy [3], and [1] in every 200 to 400pregnancy in Brazilian women; this is a 5 to10 fold higher incidence than that found in the United State of America and Europe [4][5]. The rates in Asia much higher, it's up to one in 100 pregnancies in Indonesia [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that it appears to be safe to follow patients with molar pregnancy and hCG serum levels raised but falling at 6 months after uterine evacuation, with 80.2% of these patients achieving hormonal remission in a median of 8 months. Our observation is similar to others, but is in contrast to FIGO criteria that recommend the beginning of chemotherapy treatment for these patients [9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 88%
“…The most common reason for the diagnosis of postmolar GTN and the start of chemotherapy is a plateau or rise in hCG values [10]. However, some investigators have indicated that it is safe to maintain hormonal surveillance among patients with molar pregnancy whose hCG levels are raised but falling beyond the 6 months after uterine evacuation and that spontaneous remission will occur in most cases without chemotherapy [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The most common criteria for the start of chemotherapy for GTN are hCG plateau or rise in hCG values [10]. However, there is controversy as to whether chemotherapy should be initiated for patients with molar pregnancy whose hCG levels are raised but falling beyond the 6 months after uterine evacuation, since spontaneous remission will occur in most cases without treatment [10,11]. While there is no controversy to initiate chemotherapy for patients who present with metastatic GCC and an elevated hCG, some patients with pathological diagnosis of GCC are referred to the BRCGTD with normal hCG values and no evidence of metastasis.…”
Section: Introductionmentioning
confidence: 99%